TOUCH FREE USER INTERFACE FOR AUGMENTED REALITY SYSTEMS - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Augmented Reality is the upcoming field of research and is often suffer from the current form of user interface. In this study we present touch free user interactive system for augmented reality applications to carry out multi task operations. We validated the efficacy of the method based on the performance of several users while carrying out complex task in our sample augmented reality game.Â Â Â Â